(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article presents the results of a phytochemical analysis conducted to identify flavonoid compounds present in Crataegus turkestanica (Turkestan hawthorn) using high-performance liquid chromatography (HPLC). The study aims to quantify key bioactive flavonoids, including rutin, salicylic acid, quercetin, apigenin, and kaempferol, which contribute to the plant’s medicinal potential. The findings provide insight into the chemical composition of C. turkestanica and support its traditional use in herbal medicine. The results may serve as a scientific basis for future applications in pharmaceutical and nutraceutical development.